Deep Dehydration as a Plausible Mechanism of the 2013 Mw 8.3 Sea of Okhotsk Deep-Focus Earthquake - Zhang, Hao; van der Lee, Suzan; Bina, Craig R.; Ge, Zengxi (Frontiers in Earth Science, 2021)
The rupture mechanisms of deep-focus (> 300 km) earthquakes in subducting slabs of oceanic lithosphere are not well understood and different from brittle failure associated with shallow (< 70 km) earthquakes. Here, we argue that dehydration embrittlement, often invoked as a mechanism for intermediate-depth earthquakes, is a plausible alternative model for this deep earthquake. Our argument is based upon the orientation and size of the plane that ruptured during the deep, 2013 Mw 8.3 Sea of Okhotsk earthquake, its rupture velocity and radiation efficiency, as well as diverse evidence of water subducting as deep as the transition zone and below. The rupture process of this earthquake has been inferred from back-projecting dual-band seismograms recorded at hundreds of seismic stations in North America and Europe, as well as by fitting P-wave trains recorded at dozens of globally distributed stations. If our inferences are correct, the entirety of the subducting Pacific lithosphere cannot be completely dry at deep, transition-zone depths, and other deep-focus earthquakes may also be associated with deep dehydration reactions.